A Problem Evaluation of Algorithm for Secure Node Authentication in Wireless Sensor Network - Kaur, Jatinder; Kahlon, Navroz (International Journal of Computer Sciences and Engineering, 2025)
The Wireless sensor is an improved technology for gathering highly sensitive information. Wireless sensor devices are used to gather this information with the help of sensing nodes. These devices are used in various fields but the rapid consumption of energy in wireless network and its usage is still a challenge for researchers. This paper has been designed to provide the security to user credentials as well as private key distribution for the data transmission of secure. We are proposing a new algorithm in this research paper to trim down the consumption of energy as well as to provide security in the network. It will improve the lifespan of the network